Small Scale Enterprise Workers Require Attention: What Predicts the Level of Occupational Injuries? - Chala Daba; Amanuel Atamo; Mesfin Gebrehiwot (SAGE Publishing, 2022)
Background: Occupational injuries are among the foremost public health problems that small scale enterprise workers are encountering. Most foregoing occupational injury studies focused on construction or welding industry workers which could underestimate the real level of occupational injuries recorded in small scale enterprises. Conversely, others deal with a combined level of injuries from both small scale and large scale enterprises. Therefore, this study examined the magnitude and predictors of occupational injuries among various categories of small scale enterprise workers in Ambo town (Ethiopia). Methods: An institutional-based cross-sectional study was employed among 408 small scale enterprise workers from September to October 2021. A multivariable logistic regression analysis was computed to identify factors associated with occupational injuries. Variables with P -value less than .05 were considered as significantly associated with occupational injuries. Results: The 1-year prevalence of occupational injuries was 39.5% (95% CI: 35-44). Age greater than 40 years (AOR = 2.84, 95% CI: 1.53-5.28), working for more than 8 hours per day (AOR = 2.2, 95% CI: 1.61-4.95), working during the night time (AOR = 2.1, 95% CI: 1.22-3.47), lack of workplace supervision (AOR = 2.55, 95% CI: 1.23-5.28), alcohol use (AOR = 1.95, 95% CI: 1.24-3.06), chewing khat (AOR = 2.01, 95% CI: 1.27-3.2), non-utilization of personal protective equipment (AOR = 1.55, 95% CI: 1.03-2.87), and lack of health and safety training (AOR = 2.05, 95% CI: 1.26-4.37) were important predictors of occupational injuries. Conclusions: Our findings indicated a substantial proportion of small scale enterprise workers experienced occupational injuries during the last year. Provision of health and safety training, continuous workplace supervisions, and provision and utilization of personal protective equipment are recommended.